3,4,5-Trihydroxy-N '-(1H-indol-2-yl-methylidene)benzohydrazide-1H-indole-2-carbaldehyde azine-methanol (2/1/2) - Khaledi, Hamid; Alhadi, Abeer A.; Ali, Hapipah Mohd; Robinson, Ward T.; Abdulla, Mahmood A. (International Union of Crystallography, 2010)
The title compound, 2C(16)H(13)N(3)O(4)center dot C(18)H(14)N(4)center dot 2CH(4)O, was crystallized from the reaction between 3,4,5-trihydroxy-benzoylhydrazine and indole-2-carbaldehyde in a mixture of ethanol and methanol. The compound is a stoichiometric 2:1 cocrystal of the methanol-solvated reaction product, 3,4,5-trihydroxy-N'-(1H-indol-2-ylmethylidene) benzohydrazide and 1H-indole-2-carbaldehyde azine that arose unexpectedly during the synthesis. The former molecules are linked by O-H center dot center dot center dot O hydrogen bonds and also by pi-pi stacking interactions between benzoylhydrazide rings into a two-dimensional network. The methanol solvent molecules are hydrogen bonded to this network. The centrosymmetric azine molecules are not engaged in hydrogen bonding.